Building resilience to stress through leisure activities: a qualitative analysis. Issue 4 (8th August 2017) - Denovan, Andrew; Macaskill, Ann
ABSTRACT: Stress is prevalent in modern society and coping strategies largely determine well-being. A qualitative investigation of leisure as a positive coping response to stress was undertaken using a resilience-based perspective. This approach enabled a focus on competencies and strengths in the stress-leisure-coping process, contributing to the sparse literature in this area. In-depth interviews were conducted with a sample of eight participants. From a thematic analysis three overall themes emerged: leisure as a buffer of stress, the relationship between negative and positive emotions and leisure, and benefits of leisure for coping with stress. The findings demonstrate how leisure facilitates a sense of resilience and its preventative functions. The results are discussed in relation to relevant theoretical propositions concerning the role of positive emotion in coping. In particular, the broaden-and-build theory provided a meaningful framework for suggesting how leisure and positive emotions acted in tandem to develop psychosocial resources over time.